The Effect of Sleep on Children's Word Retention and Generalization - Axelsson, Emma L.; Williams, Sophie E.; Horst, Jessica S. (Frontiers in Psychology, 2016)
In the first few years of life children spend a good proportion of time sleeping as well as acquiring the meanings of hundreds of words and their related associations. There is now ample evidence of the effects of sleep on memory in adults and the number of studies demonstrating the effects of napping and nocturnal sleep in children is also mounting. In particular, sleep appears to benefit children’s memory for recently-encountered novel words. The effect of sleep on children’s generalization of novel words across multiple items, however, is less clear. Given that sleep is polyphasic in the early years, made up of multiple episodes, and children’s word learning is gradual and strengthened slowly over time, it is highly plausible that sleep is a strong candidate in supporting children’s memory for novel words. Importantly, it appears that when children sleep shortly after exposure to novel word-object pairs retention is better than if sleep is delayed, suggesting that napping plays a vital role in long-term word retention for young children. Word learning is a complex, challenging and important part of development, thus the role that sleep plays in children’s retention of novel words is worthy of attention. As such, ensuring children get sufficient good quality sleep and regular opportunities to nap may be critical for strong language acquisition.